Peningkatan Kemampuan Motorik Kasar Anak Usia 5-6 Tahun Melalui Senam Irama - Siti Mariam Mariam; Sadaruddin Sadaruddin; Ashar Ashar (Ihya Ulum: Early Childhood Education Journal, 2025)
This research is motivated by the low gross motor skills of children aged 5-6 years at Batara Bira Kindergarten, Makassar, which is attributed to the dominance of cognitive academic activities and a lack of programmed physical stimulation. Initial observations revealed that 63% of the children (7 out of 11) exhibited passive behavior and faced serious challenges regarding coordination and body balance. This study aims to improve children's gross motor skills through the application of a modified rhythmic gymnastics method. The research method employed is Classroom Action Research (CAR) following the Kemmis and McTaggart model, conducted in two cycles. The research subjects consisted of 11 students from Group B. Data were collected through participatory observation using a gross motor development checklist instrument, which includes indicators of active participation, controlled movement, and anticipatory ability. Data analysis was performed using a comparative descriptive technique to compare achievements across cycles. The results indicated a significant improvement in children's gross motor skills. In the pre-action stage, the average classical achievement was only 28% (categorized as "Starting to Develop"). Following the intervention in Cycle I, the achievement rose to 51.5% ("Developing as Expected"), and surged drastically in Cycle II to 87.8% ("Developing Very Well"). The most notable improvements occurred in the children's anticipatory abilities and dynamic balance. This study concludes that the implementation of rhythmic gymnastics, accompanied by attractive music and age-appropriate movement variations, is effective in optimizing large muscle coordination and physical motivation in children. These results recommend the integration of rhythmic gymnastics into the daily early childhood education curriculum as a solution for enhancing physical-motor competence.